2014
DOI: 10.1002/acr.22346
|View full text |Cite
|
Sign up to set email alerts
|

United States Adults Meeting 2010 American College of Rheumatology Criteria for Treatment and Prevention of Glucocorticoid‐Induced Osteoporosis

Abstract: Objective. The American College of Rheumatology (ACR) updated its guidelines on the prevention and treatment of glucocorticoid-induced osteoporosis (GIO) in 2010. An unknown proportion of US adults at risk of fracture due to glucocorticoid use would be recommended antiosteoporosis pharmaceutical (AOP) therapies based on the ACR guidelines. Methods. Using the 2005-2010 National Health and Nutrition Examination Survey (NHANES) data for postmenopausal women (PMW), and men age >50 years reporting current glucocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…The uptake of DXA in this population was 61.0 and 30.1 %, respectively. Rates of reported current or previous GC treatment was in concord with previously reported rates from Denmark (4.5 % among women, [12]) and also comparable to earlier reported rates of previous (4.5 % [24]) and current reported CG use of 0.5-1.2 % [25]. Uptake of DXA among women reporting CG treatment was higher than the 52.3 % reported by Rubin et al for women [12] and higher than reported rates for men in Denmark of 10-15 % [13].…”
Section: Discussionsupporting
confidence: 91%
“…The uptake of DXA in this population was 61.0 and 30.1 %, respectively. Rates of reported current or previous GC treatment was in concord with previously reported rates from Denmark (4.5 % among women, [12]) and also comparable to earlier reported rates of previous (4.5 % [24]) and current reported CG use of 0.5-1.2 % [25]. Uptake of DXA among women reporting CG treatment was higher than the 52.3 % reported by Rubin et al for women [12] and higher than reported rates for men in Denmark of 10-15 % [13].…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that long-term administration of glucocorticoids can lead to GIO. 35 Glucocorticoids suppress bone formation through their direct and indirect effects on osteoblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the principal role of REDD1 in glucocorticoid function and the prevalent use of glucocorticoids by insulin-resistant cohorts (e.g., obese, T2D, aged) (56,57), little has been established about REDD1 in relation to insulin action. Moreover, the same stressors that upregulate REDD1 expression, such as glucocorticoids (75), DNA damage (42), endoplasmic reticulum stress (61,76), and hypoxia (7,65), are the same stressors that are observed in obese individuals (1,16,47) and inhibit mTOR function (7,23,75).…”
mentioning
confidence: 99%